Cognitive and affective behaviors of effective language teachers - Manalo, Eppie A. (Education quarterly.)
This study identified the variables that contribute to successful language learning. This study involved twenty-four (24) grades five (5) and six (6) elementary school teachers. Compared to typical English teachers, outstanding teachers exhibit more positive socio-affective behavior and feedback. They are organized in their activities, and they employ more facilitating strategies to make their inputs more comprehensible. They also engage their pupils in highly cognitive exercises and employ more positive but covert means of dealing with pupil errors.